TUMBUHAN HERBA DI KAWASAN TAHURA POCUT MERAH INTAN ACEH BESAR - Mariyamah, Anggia Putri; Yuliani, Riska; Eriawati, Eriawati; Amin, Nurdin (Prosiding Seminar Nasional Biologi, Teknologi dan Kependidikan, 2024)
Pocut Merah Intan Botanical Forest Park (Tahura) in Aceh Besar has many plant species, including herbaceous plants. This study aims to identify the types of herbaceous plants in this area and see their distribution patterns in various local ecosystems. The research method used field surveys, sampling, and taxonomic analysis using reference books. The results of the study found 10 species of herbaceous plants from 8 families consisting of Euphorbiaceae, Asteraceae, Rubiaceae, Poaceae, Convolvulaceae, Cyperaceae, Araceae, Orchidaceae. most dominant family Poaceae, and Araceae, most dominant family Poaceae, Fabaceae, and Asteraceae. The conclusion of this study shows the importance of maintaining herbaceous plant diversity because of its benefits to the ecosystem and its economic and medicinal potential. This study provides preliminary data for further research and management of conservation areas.